2022
DOI: 10.3390/ijms232112920
|View full text |Cite
|
Sign up to set email alerts
|

Absence of CCR2 Promotes Proliferation of Alveolar Macrophages That Control Lung Inflammation in Acute Respiratory Distress Syndrome in Mice

Abstract: Acute respiratory distress syndrome (ARDS) consists of uncontrolled inflammation that causes hypoxemia and reduced lung compliance. Since it is a complex process, not all details have been elucidated yet. In a well-controlled experimental murine model of lipopolysaccharide (LPS)-induced ARDS, the activity and viability of macrophages and neutrophils dictate the beginning and end phases of lung inflammation. C-C chemokine receptor type 2 (CCR2) is a critical chemokine receptor that mediates monocyte/macrophage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…In endotoxin exposure models of lung injury, several studies have also demonstrated that there is a decrease in the endotoxininduced recruitment of peripheral blood monocytes, exudative macrophages, F4/80 + lung cells, lung neutrophils, and lung cell in ltrates in CCR2 KO mice as well as mice depleted of systemic monocytes by clodronate liposomes (25,(50)(51)(52)(53)(54). Our studies con rm the reduction in in ltrating monocytes/macrophages with both the CCR2 KO and the administration clodronate liposomes, but also simultaneously highlight striking differences in these modeling approaches to reduce pro brotic and in ammatory responses following LPS exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In endotoxin exposure models of lung injury, several studies have also demonstrated that there is a decrease in the endotoxininduced recruitment of peripheral blood monocytes, exudative macrophages, F4/80 + lung cells, lung neutrophils, and lung cell in ltrates in CCR2 KO mice as well as mice depleted of systemic monocytes by clodronate liposomes (25,(50)(51)(52)(53)(54). Our studies con rm the reduction in in ltrating monocytes/macrophages with both the CCR2 KO and the administration clodronate liposomes, but also simultaneously highlight striking differences in these modeling approaches to reduce pro brotic and in ammatory responses following LPS exposure.…”
Section: Discussionmentioning
confidence: 99%
“…CC motif chemokine receptor 2 (CCR2) is a critical facilitator of monocyte recruitment and activation via interaction with its high-a nity ligand CCL2 (23,24). CCR2 + monocytes play a critical role in the onset of in ammation and, upon reaching the in amed tissue, differentiate into phenotypically and functionally distinct macrophages, capable of modulating in ammatory responses (25).…”
Section: Introductionmentioning
confidence: 99%